Інформаційний потенціал маргіналій Дмитра Донцова (за чернетками авторських політичних статей) - Ковальчук, В. (Спеціальні історичні дисципліни: питання теорії та методики, 2009)
В статье исследуются маргиналии Дмитрия Донцова по черновикам статей 1930-х гг., большинство которых после Второй мировой войны автор готовил к переизданию. Освещена эволюция политических взглядов автора, его отношения к ряду исторических личностей и организаций. Д. Донцов пытался очистить свои тексты от влияния нацистской пропаганды – цитат деятелей Третьего рейха, утверждений о расах и т. д. The article deals with the marginal notes, corrections and amendments of Dmitro Dontsov’s draft copies of the 1930s; the bulk of them were prepared for republication after World War II. It sheds light on the evolution process related to the author’s political views, his attitude to some historical figures and organizations. Dmitro Dontsov tried to clean the texts of the Nazi propaganda: he deleted the quotations of the Nazi public figures, some statements about races, etc.